The Smiling Abbot: Rediscovering a Unique Medieval Effigial Slab. Issue 2 (3rd July 2018) - Williams, Howard; Smith, Gillian; Crane, David; Watson, Aaron
Abstract : The article reports on a newly re-discovered fragment of a recumbent effigial slab commemorating Abbot Hywel ('Howel'), most likely an abbot of the Cistercian house of Valle Crucis, near Llangollen (Denbighs.). The slab was probably carved very early in the fourteenth century, and could have covered the abbot's burial place. The stone was dislocated and fragmented at an unknown point in the abbey's history, and most likely removed from the site during the nineteenth-century clearance of the abbey ruins. It was briefly reported on in 1895 and has been lost to scholarship subsequently. If indeed from Valle Crucis, the stone is the only known effigial slab commemorating a Cistercian abbot from Wales, and a rare example from Britain. Given that few similar Cistercian abbatial monuments have been identified from elsewhere, the 'Smiling Abbot', although only a fragment, is a significant addition to the known corpus of later medieval mortuary monuments. The article discusses the provenance, dating, identification and significance of the monument, including the abbot's distinctive smile. The stone sheds new light on mortuary and commemorative practice at Valle Crucis Abbey in the early fourteenth century.